Analisis faktor yang berhubungan dengan keikutsertaan pemeriksaan deteksi dini kanker serviks metode iva pada wanita usia 30-50 tahun - Syiefa Renanda Surya; Bambang Setiaji; Endang Budiati; Sugeng Irianto; Aila Karyus (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Early detection is an activity carried out to find out early about the possibility of a person having a disease. Early detection of cervical cancer is done to detect the possibility of someone having cervical cancer. The achievement of IVA examination in Bandar Lampung is only 36.2%. from the target of 50%. Purpose: To determine the factors associated with the participation of early detection of cervical cancer by the iva method in women aged 30-50 years Method: Quantitative research with cross sectional design. The process of collecting data using a questionnaire. The study population was women aged 30-50 years in the work area of the Health Center in Bandar Lampung City, totaling 183,855 people. The number of respondent samples calculated using the Slovin formula obtained a total of 440 samples. The sampling technique in this study was probability sampling. Results: There is a relationship between knowledge and participation in VIA examination with a p-value of 0.00 and an OR value of 78.053. There is a relationship between husband support and participation in VIA examination with a p-value of 0.00 and an OR value of 72.659. There is a relationship between support from community leaders and participation in VIA testing with a p-value of 0.00 and an OR of 52.567. There is a relationship between PKK cadre support and participation in VIA examination with a p-value of 0.00 and an OR value of 62.56. PKK cadre support is the most dominant variable with an OR value of (3.493). Conclusion: There is a relationship between husband's support for participation in VIA testing, there is a relationship between support from community leaders for participation in VIA testing, there is a relationship between support from PKK cadres and participation in VIA testing. Suggestion: PKK cadres are expected to provide counseling, motivation, and assistance for WUS to conduct early detection of cervical cancer by VIA method.